PENGARUH PUPUK KOMPOS ECENG GONDOK DANMULSA ORGANIK MucunabracteataTERHADAPPERTUMBUHAN BIBIT KELAPA SAWIT(ElaeisguineensisJacq.) DI PEMBIBITAN UTAMA - Toruan, Octaviana Lumban; Nurhidayah, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The objective of the research is to study theinteraction of â€œEcengGondokâ€ compost and organic mulch of Mucunabracteataandto obtain thebestcombination treatment for the growth of palmoil seedlings in the main nursery.The research has been conducted in the Experimental Field of Agriculture Faculty, Riau University, Pekanbaru for five months from August 2016 to January 2017. The experimental units were arranged in a Completely Randomized Design (CRD) consisting of 2 treatment factors : â€œEcengGondokâ€compost (no â€œEcengGondokâ€compost, 50 g compost of â€œEcengGondokâ€ and 100 g compost of â€œEcengGondokâ€) and mulch of Mucuna bracteata (no organic mulch, 50gorganic mulch of Mucuna bracteata and 100gorganic mulch of Mucuna bracteata). Each treatment repeated 3 times so that there were 27 palm oil seedlings.Observed parameters were seedling height increment, number of leaves increment, stem diameter increment, volume of root, dry weight of seedling, number of growing weeds in the polybag. The data were analyzed with ANOVA and the means of treatments were compared with DNMRT at 5 % level. Interaction effect ofÂ â€œEcengGondokâ€compost and organic mulch of Mucuna bracteata was significant on the dry weight of seedling and thenumber of growing weeds in the polybag. Application of 100 g compost of â€œEcengGondokâ€ and 100gorganic mulch of Mucuna bracteata resulted in a better growth of palmoil seedlings.Â Keywords : Palm oil seedling, compost of â€œEcengGondokâ€, organic mulch of Mucuna bracteata